PENGARUH EKUITAS MEREK TERHADAP KEPUTUSAN PERAWATAN ULANG - Bekti Wulandari; Waluyo Budi Atmoko; Ariefah Yulandari (Conference on Innovation in Health, Accounting and Management Sciences (CIHAMS), 2020)
This study aims to determine the effect of brand equity on redrawing decisions. In purchasing decision making, a process begins when the buyer realizes that there is a need problem. Based on these needs, consumers are compelled to seek further information. Information search results in a number of alternative products to meet needs. Based on several available alternatives, consumers evaluate these alternatives, to get the best product or service according to their needs. The data were obtained through questionnaires distributed to the general public, either those who had undergone treatment or had not performed the treatment. The sample used was 200. The sampling technique used was purpose sampling. Hypothesis testing is performed using SEM (Structural Equation Modeling) analysis and logistic regression. The results in this study indicate that five hypotheses are supported. Brand equity variable has a positive effect on re-maintenance decisions. Brand awareness variable has a positive effect on brand equity. Brand association variable has a positive effect on brand equity. Brand loyalty variable has a positive effect on brand equity. Perceived quality variable has a positive effect on brand equity.